The Land and Tree Recognize the Musahar: Alternative Perspective of Nature-human Understanding among the Musahars - Giri, Madhu (THE ACADEMIA, 2025)
Natural cosmology is the largest entity in which all nature including human beings and their recycle-continuity encompassed as Hindu-Buddhist idea of the immortal soul. The soul can enter in any form of the body (tree, animal, human, bird, fish, insect, and anything) and it can interchangeably communicate with any living thing. The activities of human beings are observed, evaluated, and controlled by non-humans and vice-versa. The binary categories of nature-culture, human-non-human, civilized-savage, and lived-dead are rejected in the understanding of the natural cosmology of the Musahars. In this article, I tried to explore intersubjective relations between natural phenomena and the cultural practices of the Musahar people. I employed participatory observation and key informant interview methods including long-term ethnographic fieldwork among the Musahars people in Siraha district, Nepal. The Musahars communicate with trees, stones, lands, water, animals, and birds around the settlement. They claimed that natural phenomena understood their language, emotions, crisis, and happiness. They considered themselves as a part of a larger natural cosmology. This paper explored how the Musahars transformed themselves into wild animal, tree, birds, fish, super human (like god) and again bounced back to human. The article explores alternative epistemology to understand nature’s understanding of human behaviors. All non-human spirits could look the human and their activities through the lens of natural spirit. The concept and transformation of the Musahar people and natural phenomena or their inter-subjectivity are called Musahar’s perspectivism in this article.